URGENSI DISIPLIN DALAM PEMBELAJARAN - Ramli Abdullah (UIN AR-RANIRY, 2015)
Learning outcomes is a whole skill and the results achieved through the learning process in schools defined by the numbers measured by achievement test. While the measure is to apply the measuring instrument to a particular object. Magnitudes numbers obtained, then gained significance when compared to the measurement results to a specific benchmark. Associated with discipline in this study is the tendency to use regulation as a guide in learning a subject and a tendency consistent implementation of rules in learning a subject, and the tendency of commitment to the provision of reward and punishment in the process of studying a course. So with so that there is a positive relationship between the Discipline of the learning outcomes of a course. It means that any increase to the Discipline resulting in the increase of learning outcomes of a course. And this shows if the Disciplinary enhanced the learning outcomes of a course increases. Discipline and vice versa if lower then the learning outcomes of the course also lower suggesting that the learning outcomes of the course is determined by the Discipline. That there is a positive relationship between the discipline of the learning outcomes of a course. This means that every increase of discipline resulted in an increase learning outcomes of a course. So for that, it can be stated that the relationship between the discipline of the learning outcomes of the course well. This shows if the discipline improved the learning outcomes of the course increased as well.